Pregnancies in infertile couples. - Jefferson, Luz (2015)
Human reproduction is an important phenomenon in the perpetuation of life and important also in terms of its social and human implications. According to estimates, it is considered that in a population there 10-15% of couples who can not fulfill this role. We do not know whether in developing countries or rather underdeveloped countries where social and economic conditions have intimate relationship with the levels of nutrition, education, housing, sanitation, health (especially regarding the presence of infectious diseases), percentage of infertile couples is higher. There are no epidemiological studies that inform us about it.